Digital Transformation: Quality of Online Claim Services and Participant Satisfaction at BPJS Ketenagakerjaan, Manado Branch - Samiun, Nur Ida; Azzochrah, Nurul Azizah; Haris, Chadijah (Maqrizi: Journal of Economics and Islamic Economics, 2024)
Digital Transformation has become a global phenomenon affecting various aspects of life, including public services. This study aims to analyze the impact of online claim service quality on the satisfaction of BPJS Ketenagakerjaan participants at the Manado Branch. The study fills a gap in the literature by specifically addressing participant satisfaction at the BPJS Ketenagakerjaan Manado Branch. The proposed hypothesis is that high-quality online claim services positively influence participant satisfaction. The research method used is a quantitative approach with a survey method, employing questionnaires to collect data from 99 respondents. Validity and reliability tests showed that the instruments used are valid and reliable. Simple linear regression analysis indicates that the quality of online claim services has a positive and significant effect on participant satisfaction. However, about 54% of the variation in participant satisfaction cannot be explained by service quality alone, indicating other factors need to be considered to enhance participant satisfaction in the future. The conclusion of this study underscores the importance of online claim service quality in increasing participant satisfaction but also highlights the need to consider other factors. Practical implications for service providers include improving service quality through process optimization, increasing response speed, providing accurate and easily accessible information, and managing participant expectations through clear communication regarding the claim process and completion time.